Stanford Type A Acute Retrograde Aortic Dissections: From Surgical to Endovascular Strategy?. Issue 4 (30th October 2015) - Follis, Fabrizio; Raffa, Giuseppe M.; D'Ancona, Giuseppe; Amaducci, Andrea; Follis, Marco
Abstract: Acute type A retrograde aortic dissection is characterized by a port of entry located in the descending aorta near the subclavian take‐off, and is currently treated with surgery. Our experience with two patients who underwent a complicated postoperative course stimulated a review of the current literature and discussion of possible alternative strategies in light of recent advances in endovascular treatment.